MENGOPTIMALKAN KECERDASAN EMOSIONAL DENGAN KETERAMPILAN MEMERANKAN TOKOH DALAM DRAMA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS TINGGI - Prameswari, Aisyah; Endang M Kurnianti; Susi Winarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to obtain the determinants related to optimizing the emotional intelligence of elementary school students through drama-based learning. Emotional intelligence (EQ) has an important role in the academic and social development of students, where drama as a learning medium can improve empathy, emotional control, and students' social skills. The method used is a literature study with a qualitative approach to explore the contribution of drama in learning Indonesian in high school. The results of the study of ten research objects show that the determinants of success include the right implementation strategy, managing challenges during learning, and solutions applied to optimize drama character skills. The results of the study show that drama skills can effectively support the development of students' emotional intelligence if applied with the right strategy, such as selecting relevant scripts, role guidance, and post-performance reflection. The challenges that arise include time constraints, lack of teacher training, and variations in student characters. Thus, the integration of drama in learning Indonesian is an effective strategy to develop students' emotional intelligence, while supporting the improvement of the quality of holistic and meaningful learning in elementary schools.